A Technique for Decreasing Reactivity of Coal Material to Suppress the Oxygen Absorption Process; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Timofeeva S. S. (2016, 2016)
Title screen